Deciphering the role of classical oestrogen receptor in insulin resistance and type 2 diabetes mellitus: From molecular mechanism to clinical evidence - Haryati Ahmad Hairi; Nurul Izzah Ibrahim; Muhammad Zulfiqah Sadikan; Putri Ayu Jayusman; Ahmad Nazrun Shuid (BioImpacts)
The biological actions of oestrogen are mediated by the oestrogen receptor α or β (ERα or ERβ), which are members of a broad nuclear receptor superfamily. Numerous in vivo and in vitro studies have demonstrated that loss of circulating oestrogen modulated by classical ERα and ERβ led to rapid changes in pancreatic β-cell and islet function, GLUT4 expression, insulin sensitivity and glucose tolerance, dysfunctional lipid homeostasis, oxidative stress, and inflammatory cascades. Remarkably, 17β-oestradiol (E2) can completely reverse these effects. This review evaluates the current understanding of the protective role of classical ER in critical pathways and molecular mechanisms associated with insulin resistance and type 2 diabetes mellitus (T2DM). It also examines the effectiveness of menopausal hormone therapy (MHT) in reducing the risk of developing T2DM in menopausal women. Clinical trials have shown the protective effects of MHT on glucose metabolism, which may be useful to treat T2DM in perimenopausal women. However, there are concerns about E2's potential side effects of obesity and hyperlipidaemia in menopausal women. Further studies are warranted to gain understanding and find other oestrogen alternatives for treatment of insulin resistance and T2DM in postmenopausal women.